PENGARUH PEMBELAJARAN PENDIDIKAN PANCASILA TERHADAP CIVIC SKILL PADA SISWA KELAS VIII SMP NEGERI 12 PEKANBARU - Olyvia Rosalia; Hambali; Supentri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of Pancasila Education learning on civic skills of class VIII students of State Junior High School (SMPN) 12 Pekanbaru. Civic skills are skills that include students' intellectual and participatory abilities in national and state life, including critical thinking, active participation, and understanding the rights and obligations as citizens. This study consists of 2 (two) variables, namely: Pancasila Education (variable x) and Civic Skill (variable y). The research method used is quantitative with a statistical approach. The sample consisted of 62 students of class VIII.7 and VIII.8 who were selected through a total sampling technique. The results of data analysis using the F test showed a calculated F value of 70.334 which was greater than the F table of 4.001, which means that there is a significant influence between Pancasila Education learning on students' civic skills. The correlation coefficient value (r) of 0.735 indicates a strong and positive relationship, while the determination coefficient value (R- square) of 54% indicates that Pancasila Education has an influence on civic skills. The remaining 46% is influenced by other factors not examined in this study. These results emphasize the importance of integrating Pancasila values in learning in order to form students' democratic, responsible, and active characters in community and state life.